Medicine and wagering: same terms, different concepts. - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2013)
Medicine and wagering are apparently distant contexts. However, they share a number of basic terms and expressions. In effect, shaping estimates and making forecasts are fundamental tasks common both to medicine and betting. In conclusion, a series of terms are used both in medicine and wagering, and the analogous statistical roots and the common necessity of computing risks and formulating predictions explain the presence of the same terms, indicating the permeability of the medical context to the insertion of terminology taken from other fields. Obviously, the meaning and application of words change in the two contexts, as the history of medicine well documents.